2011
DOI: 10.1242/jeb.061747
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity during the frenzy swim: analysing early swimming behaviour in hatchling sea turtles

Abstract: SUMMARYSwimming effort of hatchling sea turtles varies across species. In this study we analysed how swim thrust is produced in terms of power stroke rate, mean maximum thrust per power stroke and percentage of time spent power stroking throughout the first 18h of swimming after entering the water, in both loggerhead and flatback turtle hatchlings and compared this with previous data from green turtle hatchlings. Loggerhead and green turtle hatchlings had similar power stroke rates and percentage of time spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…This study suggests that anaerobic metabolism in flatback hatchlings is similar or slightly higher than that of loggerhead hatchlings, however Pereira et al (2011) showed that swimming effort is relatively lower in flatback turtle hatchlings than in loggerhead turtles hatchlings. This suggests that it is the aerobic component of flatback hatchling swimming effort that is relatively lower in comparison with loggerhead hatchlings.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…This study suggests that anaerobic metabolism in flatback hatchlings is similar or slightly higher than that of loggerhead hatchlings, however Pereira et al (2011) showed that swimming effort is relatively lower in flatback turtle hatchlings than in loggerhead turtles hatchlings. This suggests that it is the aerobic component of flatback hatchling swimming effort that is relatively lower in comparison with loggerhead hatchlings.…”
Section: Discussionmentioning
confidence: 48%
“…In this study I proposed that loggerhead turtle hatchlings would experience intermediate changes in these physiological variables as a result of their moderate swimming effort, whereas flatback turtle hatchlings would experience smaller changes given their relative low swimming effort, as suggested by previous studies (Pereira et al, 2011;Pereira et al, 2012) concentrations at different times during the beach crawl and early stages of the swimming frenzy in hatchling sea turtles Baldwin et al, 1989;.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations